Metacognition in Autism Spectrum Disorder: Digital Technologies in Metacognitive Skills Training - Mitsea, Eleni; Drigas, Athanasios; Skianis, Charalampos (Technium Social Sciences Journal, 2022)
Extensive research has been conducted regarding socio-emotional skills training in autism spectrum disorder (ASD). The latest autism research is now beginning to recognize the role of metacognitive deficits in ASD as well as the importance of metacognitive skills training in autism intervention. The purpose of the current review study is to shed light on the role of metacognition in ASD and identify assistive technologies that may compensate for metacognitive deficits in ASD. Specifically, we examine autism through the lens of the models of metacognition developed by (Drigas and Mitsea, 2020;2021). Following these metacognitive models, we identified digital technologies that have the significant potential to train metacognitive skills in people with ASD. These technologies include, among others, robotics, virtual reality, mobile applications, digital serious games, coding digital games and robots. This review provides evidence that people with autism face important difficulties in almost all metacognitive domains. It also highlights that digital technologies are effective tools for training metacognitive skills in ASD. This study is one of the few studies that deal with autism as a disorder of metacognition and gives pointers for future experimental research regarding intervention strategies with the assistance of technologies.